BOOK ANALYSIS WITH THEMA GEOPOLITICS â€œMEDIA, TERRORISM AND THEORYâ€, A CRITICAL THEORY RESEARCH APPROACH USING SEMIOTIC ANALYSIS - Deddy Tobing; Henny Saptatia (Jurnal Ilmiah Publipreneur, 2020)
This article seeks to create a discussion space related to the Media Book, Terrorism and Theory. This book seeks to provide an understanding of the contextualization of the global cycle of violence within the framework of "military action" and "terrorism," as well as mass communication media. The author tries to view this book as a literary work by using semiotic analysis to get the meanings in this book, especially in the sections Critical Media Theory, Democratic Communication, and Global Conflict and Chapter 8 with the title Terrorism, Public Relations and Propaganda. This research finally succeeded in achieving an evaluation that some myths were generated from the meaning of denotation and connotation of Roland Barthes' semiotic technique. These myths when tested through the source triangulation technique show inconsistencies. Some of the myths are discussed by academics and the media, but some do not appear in the media.